Playing it safe? Behavioural responses of mosquito larvae encountering a fish predator. Issue 1 (2nd January 2018) - Chandrasegaran, Karthikeyan; Singh, Avehi; Laha, Moumita; Quader, Suhel
Abstract : Predation is a strong selective force that affects prey population and ecosystem dynamics. Detecting predators and associated levels of threat is crucial to prey responses. Once a predator is detected, anti-predatory responses improve the chances of survival of prey. We used Aedes aegypti larvae to study behavioural responses to predation threat from guppies ( Poecilia reticulata ). Specifically, we tested the relative importance of chemical cues, both in isolation and in combination with physical cues, in eliciting anti-predatory behaviours. Larvae responded more strongly, by reducing the lengths of their wriggle bursts, when presented with a combination of chemical and physical cues than with chemical cues alone. Anti-predatory responses often come with an associated cost, and we expect that the ability to pay these costs should influence responses to predation risk. To test this, we compared wriggling patterns of satiated vs starved larvae in the same experiment. We found that, under predation risk, starved larvae were willing to take more risks than satiated larvae were. We sought to experimentally test the assumption that anti-predator behaviours increase the survival of prey. To do this, starved guppies were made to choose between displays of simulated larvae, moving in short and long wriggle bursts as observed in the previous experiment. The fish preferentially attacked larvae moving in long bursts, demonstrating the survival value of the larval anti-predatory response of shifting to a preponderance of short wriggle bursts. Our study identifies specific ways in which trade-offs between predation risk and energetic costs could affect anti-predator behaviour.